Unveiling Research Trends in Philippine Mathematics Education: A Comprehensive Bibliometric and Systematic Analysis - Acopio, Ma. Kathleen Mae Geremias (Jurnal Pendidikan Progresif, 2025)
Unveiling Research Trends in Philippine Mathematics Education: A Comprehensive Bibliometric and Systematic Analysis. Objectives: This study aimed to conduct a bibliometric analysis of mathematics education research affiliated with the Philippines, as indexed in the Scopus database, covering the period from 2006 to 2024. The objective was to map publication trends, identify prolific authors and institutions, and analyze thematic and disciplinary classifications to assess the country’s research visibility and productivity. Methods: Data were retrieved from the Scopus database due to its comprehensive coverage of peer-reviewed academic publications. The search query used was: AFFILCOUNTRY ("Philippines") AND (SUBJAREA (educ) OR SUBJAREA (math)) AND TITLE-ABS-KEY ("mathematics education" OR "mathematics teaching"). A total of 25 documents were initially retrieved. After screening for duplicates, non-English records, and incomplete metadata, 20 documents were retained for analysis. The metadata were processed using Elsevier’s SciVal and VOSviewer to examine publication output, author productivity, institutional affiliations, document types, subject areas, and keyword co-occurrences. Findings: The results revealed minimal research output before 2020, followed by a marked increase beginning in 2020, coinciding with the global shift to remote and hybrid learning due to the COVID-19 pandemic. Research productivity remains highly concentrated, with the top three institutions Ateneo de Manila University, Philippine Normal University, and De La Salle University accounting for over 50% of total publications. Most documents were journal articles, and the predominant subject areas were mathematics and education, with emerging interdisciplinary themes related to digital learning and abstraction. Conclusion: While recent gains in research output are promising, Philippine mathematics education scholarship remains uneven. Expanding research capacity, fostering regional collaboration, and utilizing bibliometric tools are essential steps toward improving research equity, visibility, and impact at both national and global levels. Keywords: mathematics education, bibliometric analysis, Philippines, COVID-19, research productivity, international visibility.